Struggle for Military Leadership in Tsaritsyn in May–July 1918 - Mikhail D. Shumakov (Historia provinciae: журнал региональной истории)
The article deals with the problem of rivalry between various political and military figures for the right to lead troops in the Tsaritsyn area in the period between late spring and mid-summer of 1918. The main sources of the article include published and unpublished memoirs of the participants in the events, records and telegrams of Tsaritsyn government agencies and political figures. On the basis of both well-known sources and those introduced into scholarly discourse for the first time, the author analyzes the confrontation between the members of the local military authority, the Defense Headquarters of the Soviets, and the leadership of the North Caucasus Military District (SKVO) who had been sent from Moscow. Until a certain moment, the struggle had not led to a clear victory of either party. The author points out that Stalin who arrived in Tsaritsyn on June 6, 1918 quickly began to take steps to concentrate the military leadership in his own hands. Two forces rendered him his main support in the process: the leaders of the local government, primarily S. Minin, and the troops under the command of K. Voroshilov, who retreated to Tsaritsyn from Donbas. The author of the article focuses on the rapidly emerging conflict between these two forces. It led to the fact that people from Voroshilov’s entourage found themselves in many leadership positions in Tsaritsyn, and the key appointments are retraced in the article. Stalin managed to use the balance of two forces, the local government and Voroshilov’s group, to attack the leadership of the North Caucasus Military District. It resulted in the formation of the SKVO Military Council, which headed the solution of all military issues in the district. The Military Council included J. Stalin, S. Minin, and K. Voroshilov. Within the framework of the facts presented in the article, the author considers this membership as a reflection of the balance of key political forces present in Tsaritsyn during the period under study.